Docência e gênero: um estudo sobre o professor homem na educação infantil da Rede Municipal de Ensino de Tocantinópolis - TO - Ferreira, Erisvaldo Alves (Universidade Federal do Tocantins, 2024)
The difference between the number of men and women working in early childhood education in the brazilian context is visible. By common sense this responsibility - for the education and care of young children - is imposed on women, because they were born with the "gift" of being a mother, and also because their activities at home are considered equivalent to those performed in institutions of early childhood education. This work, therefore, analyzes the male presence in teaching in early childhood education in the context of the city of Tocantinópolis, in the interior of the state of Tocantins. The question that guides this monography is “what are the impacts of the male presence in teaching in early childhood education in the context of the city of Tocantinópolis, interior of the state of Tocantins?”. The research method used to answer this question was a bibliographical survey (about early childhood education in Brazil and about gender studies) and the application of questionnaires with employees (men and women) who work in early childhood education in the city. Regarding the results found, we highlight the presence of two male teachers working in early childhood education in the municipality; as well as their good reception (by fellow teachers, coordinators and students' parents) in the performance of their duties.